2019
DOI: 10.1007/s10544-019-0424-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biological synthesized platinum nanoparticles using Ononidis radix extract on the cell lung carcinoma A549

Abstract: Due to the search for new methods for synthesizing nanomaterials, this work proposes the biological synthesis of platinum nanoparticles using Ononidis radix extract. The synthesized platinum nanoparticles were characterized by UV-Vis, Scanning Electron Microscopy (SEM) with EDS profile, Fourier transform infrared spectroscopy (FTIR), Transmission Electron Microscopy (TEM) and Atomic Force Microscopy (AFM). The examination conducted by means of Transmission Electron Microscopy showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The presence of flavonoids is very significant for the formation Au/ZnO/Ag nanoparticles. The antioxidant activity of flavonoid compounds is associated with the ring-shaped structure of the particle, which contains conjugated double bonds, as well as with the presence of various functional groups in the rings [ 14 ]. Flavonoids exhibit antioxidant properties due a considerable number of hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of flavonoids is very significant for the formation Au/ZnO/Ag nanoparticles. The antioxidant activity of flavonoid compounds is associated with the ring-shaped structure of the particle, which contains conjugated double bonds, as well as with the presence of various functional groups in the rings [ 14 ]. Flavonoids exhibit antioxidant properties due a considerable number of hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods for synthesizing metal nanoparticles include physical vapor deposition, chemical vapor deposition, sol–gel method, microwave-assisted synthesis, ultrasonication method, electrochemical synthesis, and chemical reduction of metallic ions [ 13 ]. For several years, metallic nanoparticles have been produced using low-cost, energy-efficient and non-toxic methods utilizing plants, algae, fungi, bacteria and viruses [ 14 ]. The application of phytochemicals for the purpose of synthesizing nanoparticles represents a significant symbiosis between nanotechnology and green chemistry [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platinum nanoparticles (PtNPs) have been widely used in oxidation and hydrogenation reactions in petrochemical industry, due to their large surface and many other characteristics that encourage to synthesize PtNPs for catalytical applications. Therefore, there is a high demand for synthesis of PtNPs using of eco-friendly materials [177,[200][201][202][203][204][205].…”
Section: Platinum Nanoparticlesmentioning
confidence: 99%
“…The anticancer activity of the biosynthesized PtNPs was evaluated against A549 cancer cell lines. The maximum cell mortality of 8.8% was observed at an incubation time of 72 h and a concentration of 100 µg/mL of PtNPs [74]. Ullah et al reported the synthesis of spherical PtNPs of size 5 nm utilizing leaf extract of Maytenus royleanus.…”
Section: Characterization and Biological Activities Of Ptnps Prepared Using Plant Extractsmentioning
confidence: 99%